Myosin light chains and the developmental origin of fast muscle. - Stockdale, F E (1981)
Physiological characteristics of embryonic and fetal fast muscle function are similar to those of adult slow muscles, whereas most biochemical data suggest that embryonic and fetal fast muscles contain only fast muscle myosin. In the studies reported here, myofibrillar preparations from developing avian pectoral muscle (fast muscle) were isolated and analyzed for myosin light-chain type and synthesis. These analyses show that early in development avian fast muscle synthesizes and assembles myofibrils with light chains of both slow and fast myosins. Later in development, fast muscle no longer assembles myofibrils containing slow myosin light chains due to the cessation of synthesis of slow myosin light chains in mid-development. These in vivo studies indicate that the more developmentally primitive type of skeletal muscle is one that synthesizes both slow and fast myosin light chains independent of its anatomic location, and an event(s) late in fast muscle development results in the repression of synthesis of slow myosin light chains.